Bronchopulmonary dysplasia is associated with reduced oral nitrate reductase activity in extremely preterm infants - Gentle, Samuel J. (Redox Biol, 2020)
Oral microbiome mediated nitrate reductase (NR) activity regulates nitric oxide (NO) bioavailability and signaling. While deficits in NO-bioavailability impact several morbidities of extreme prematurity including bronchopulmonary dysplasia (BPD), whether oral NR activity is associated with morbidities of prematurity is not known. We characterized NR activity in extremely preterm infants from birth until 34 weeks' post menstrual age (PMA), determined whether changes in the oral microbiome contribute to changes in NR activity, and determined whether changes in NR activity correlated with disease. In this single center prospective cohort study (n = 28), we observed two surprising findings: (1) NR activity unexpectedly peaked at 29 weeks' PMA (p < 0.05) and (2) when infants were stratified for BPD status, infants who developed BPD had significantly less NR activity at 29 weeks’ PMA compared to infants who did not develop BPD. Oral microbiota and NR activity may play a role in BPD development in extremely preterm infants, indicating potential for disease prediction and therapeutic targeting.